2013
DOI: 10.1097/inf.0b013e31829baae0
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Clinical Characteristics of Campylobacter Bacteremia in Children With and Without Predisposing Factors

Abstract: Childhood CB is rare in southern Israel. The disease manifests as a single gastroenteritis complication in a previously healthy young child or as recurrent episodes in an older, immune-compromised child, usually without gastrointestinal symptoms. This disparity may reflect pathogenesis differences, with disease in the immune-competent being dependent on pathogen virulence, whereas disease in the immune-compromised being host dependent. Disease outcome is usually favorable, and macrolides remain the antibiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…We found two cases of bacteraemia due to Campylobacter. Very few previous studies have described Campylobacter bacteraemia in Israel or elsewhere [9][10][11] . Bacteraemia is a rare finding of Campylobacter gastroenteritis in immunocompetent children, but it has been found in several cases of immunocompromised children.…”
Section: Discussionmentioning
confidence: 99%
“…We found two cases of bacteraemia due to Campylobacter. Very few previous studies have described Campylobacter bacteraemia in Israel or elsewhere [9][10][11] . Bacteraemia is a rare finding of Campylobacter gastroenteritis in immunocompetent children, but it has been found in several cases of immunocompromised children.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a 10-year nationwide study in Finland concluded that C. jejuni and C. coli bacteremias affect predominately younger individuals without major underlying diseases (206). The disease generally results from a single gastroenteritis complication in children or as recurrent episodes in immunocompromised children without gastrointestinal symptoms (207). A number of Campylobacter species, including C. jejuni, C. coli, C. fetus, and C. upsaliensis, have also been associated with sepsis in both immunocompetent and immunocompromised children and adults (208)(209)(210).…”
Section: Bacteremia and Septicemiamentioning
confidence: 97%
“…The clinical manifestations of C. coli bacteremia have only rarely been reported. Previous studies have shown that patients with immunocompromising factors, like our patient, tend to suffer from recurrent C. coli bacteremia without gastrointestinal symptoms ( 7 , 31 ). Cutaneous involvement is less recognized and may often be overlooked as a presentation of Campylobacter bacteremia ( 32 ).…”
Section: Discussionmentioning
confidence: 49%